Correlation Between Concept of Stress and Coping Strategies Among Youth - Kuvaeva, I (KnE Life Sciences, 2018)
Introduction. The article presents the results of the analysis of the correlation between the structural organization of the concept of stress and coping strategies among the freshmen, studying the humanities. The research into the subjective experience of stress of this age group reflects the content structure of the representations of stress and style of coping behaviour. Method. The concept of stress has been studied by means of the directed associative experiment, which helps to describe the organisation of implicit representations of stress and difficult situations of a person. The content categories (stress-factors – state and immediate effects – consequences – stress process – stress management) were found in the respondents’ answers; the number of the presented categories is a measure of differentiation of the stress concept. Coping strategies were analysed with the application of the common form of «Adolescent Coping Scale». Results. It has been revealed that the increase in the degree of differentiation of the concept results in strengthening such strategies as ‘anxiety’, ‘not coping’, ‘tension reduction’ and ‘self-accusation’ (p ≤ 0.005); ‘content simplification’ of the concept leads to the demand in the strategy ‘social action’ (p =0.000). The stylistic specifics of coping behaviour of a student are connected with the degree of differentiation of the concept. Those students who have diverse implicit representations of stress are characterized by problem-oriented coping combined with the positive focus and tendency towards solitude. The orientation to problemsolving of the respondents, who gave incomplete descriptions of stress signs, is accompanied by a competing activity in terms of physical activity. The students, scarcely describing stress, enhance socio-oriented resources application for coping with a difficult situation. Conclusion. Practical relevance of this research consists in identifying the psychological conditions, which are necessary for effective coping among various groups of students. Keywords: stress, representations of stress, concept, coping strategies, coping behaviour, cross-cultural differences, student, youth